Experimental Study on Modulus and Hardness of Ettringite. Issue 1 (6th May 2011) - Yang, D.Y.; Guo, R.
<x xml:space="preserve">Abstract</x> The experimental study on the modulus and hardness (in‐press rigidity) of ettringite is carried out in this work. Firstly, the ettringite is obtained by chemical synthesis method. Secondly, samples are formed by filling the ettringite into resin matrix. Thirdly, the indentation modulus and hardness of ettringite are measured with different indentation depths by virtue of the instrument of MTS Nanoindenter XP. Finally, analysis on the modulus and hardness of the ettringite is performed according to the sample unloading curves. The results given by this work indicate that the magnitude of the modulus is 20.07 GPa and the hardness is 0.613 GPa.